Frequency of Coronary Artery Anomalies Among Adult Patients Undergoing Primary Percutaneous Coronary Intervention - Jawad, Muhammad; Ali, Nauman; Shahzadi, Adeela (Biological and Clinical Sciences Research Journal, 2025)
Coronary artery anomalies (CAAs) are congenital variations in coronary anatomy that may be encountered during primary percutaneous coronary intervention (PCI). Early recognition is critical to avoid procedural complications, especially during emergent interventions. Objective: To determine the frequency and types of CAAs in adult patients undergoing primary PCI in a tertiary care hospital in Pakistan. Methods: This descriptive cross-sectional study was conducted over six months at the Department of Cardiology, Bahawal Victoria Hospital (BVH), Bahawalpur, from 3rd October 2024 to 3rd April 2025. One hundred sixty-two adult patients undergoing primary PCI were included using non-probability consecutive sampling. Demographic, clinical, and angiographic data were recorded. Coronary angiograms were assessed for anomalies by two experienced interventional cardiologists. Data were analyzed using SPSS v25. Chi-square tests were applied to evaluate associations between CAAs and cardiovascular risk factors. Results: Among the 162 patients, the mean age was 58.4 ± 10.2 years, with 74.7% being male. The overall frequency of CAAs was 9.3% (n = 15). The most common anomaly was the right coronary artery (RCA) originating from the left coronary sinus (3.1%), followed by absence of the left main trunk with separate origins of the LAD and LCx arteries (2.5%). No statistically significant association was found between CAAs and hypertension (p = 0.43), diabetes mellitus (p = 0.39), smoking (p = 0.36), age > 60 years (p = 0.85), or male gender (p = 0.68). Conclusion: The frequency of CAAs in patients undergoing primary PCI in this Pakistani tertiary care setting was relatively high at 9.3%. The most frequently observed anomalies were RCA from the left coronary sinus and absence of the left main trunk. While no significant correlation was observed with traditional cardiovascular risk factors, the recognition of CAAs remains essential during emergency PCI to guide catheter selection, prevent procedural delays, and ensure patient safety.